Bushworld : Enter at Your Own Risk - Dowd, Maureen (New York G.P. Putnam's Sons, 2004)
The columnist discusses the Bush dynasty and the people surrounding the administration, including Cheney, Ashcroft, Rumsfeld, Rice, Rove, Wolfowitz, and Perle.
Keywords: United States -- Diplomatic relations -- Imperialism -- Politics and government